2018
DOI: 10.18632/oncotarget.24903
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide species are elevated in human breast cancer and are associated with less aggressiveness

Abstract: Sphingolipids have emerged as key regulatory molecules in cancer cell survival and death. Although important roles of sphingolipids in breast cancer progression have been reported in experimental models, their roles in human patients are yet to be revealed. The aim of this study was to investigate the ceramide levels and its biosynthesis pathways in human breast cancer patients. Breast cancer, peri-tumor and normal breast tissue samples were collected from surgical specimens from a series of 44 patients with b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
90
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(101 citation statements)
references
References 58 publications
(73 reference statements)
10
90
1
Order By: Relevance
“…Beyond their structural role in the membrane homeostasis, sphingolipids control critical signaling transduction pathways within the cancer cells to drive growth, proliferation, migration and invasion. Altered levels of ceramide species and other metabolites in the sphingolipid metabolism network of the cancer cells is related to the deregulation of the expression of the genes encoding the enzymes within this network (Moro et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond their structural role in the membrane homeostasis, sphingolipids control critical signaling transduction pathways within the cancer cells to drive growth, proliferation, migration and invasion. Altered levels of ceramide species and other metabolites in the sphingolipid metabolism network of the cancer cells is related to the deregulation of the expression of the genes encoding the enzymes within this network (Moro et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Sphingolipids are key regulatory bioactive molecules that play important roles in cancer biology (Ogretmen, 2018). Altered sphingolipid metabolism are linked to several cancer types including liver, colon (Selzner et al, 2001), endometrial (Knapp et al, 2010) and breast cancer (Moro et al, 2018;Nagahashi et al, 2016). The levels of sphingolipid pathway metabolites, including ceramides and sphingosine-1-phosphate (S1P), are significantly deregulated in breast tumor tissue compared to normal tissue (Moro et al, 2018;Nagahashi et al, 2016), and elevated tumor ceramide levels have been shown to be associated with higher tumor grades (Moro et al, 2018;Schiffmann et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…63 Consequently, it is thought that the life or death of a cell is regulated by the balance between S1P and ceramide. 63 However, further research is needed to determine how the balance between S1P and ceramide is regulated to maintain cell homeostasis. Together, SphK, F I G U R E 2 Metabolism of sphingolipids.…”
Section: S1p Concentration Gradient and Roles Of Degrading Enzymesmentioning
confidence: 99%
“…S1P lyase is an enzyme that decomposes S1P irreversibly . S1P phosphatase is an enzyme that removes phosphate from S1P to produce sphingosine, which can then be converted to ceramide by ceramide synthase . Whereas S1P acts as a “cell survival signal” for cell proliferation and survival, ceramide acts as a “cell death signal” for cellular apoptosis .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation